2022
DOI: 10.5751/es-12957-270118
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the institutional foundations of adaptive water governance in South India

Abstract: Institutional structures can fundamentally shape opportunities for adaptive governance of water resources at multiple ecological and societal scales. The properties of adaptive governance have been widely examined in the literature. However, there has been limited focus on how institutions can promote or hinder the emergence of adaptive governance. Elinor Ostrom's institutional theory stresses the importance of formal and informal norms and rules in effective governance of natural resources. Specifically, Ostr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 45 publications
(72 reference statements)
0
5
0
Order By: Relevance
“…In addition, the authors (Djalante et al, 2011;Knüppe, 2011) argued that the participation of relevant actors at different levels and scales encouraged the coproduction of new knowledge which enabled to develop and increase adaptation strategies in natural hazards in Nepal and groundwater management in South Africa. Both formal and informal collaboration proved Frontiers in Environmental Science frontiersin.org beneficial to the AG in water governance in India (Vallury et al, 2022). Formal collaboration facilitates regulatory capacity and access to financial and institutional resources, and informal collaboration fosters flexibility and trust in water governance processes in these regions (Evans et al, 2011;Tuda et al, 2021;Yasmin et al, 2022).…”
Section: Collaboration Across Sectors and Scalesmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, the authors (Djalante et al, 2011;Knüppe, 2011) argued that the participation of relevant actors at different levels and scales encouraged the coproduction of new knowledge which enabled to develop and increase adaptation strategies in natural hazards in Nepal and groundwater management in South Africa. Both formal and informal collaboration proved Frontiers in Environmental Science frontiersin.org beneficial to the AG in water governance in India (Vallury et al, 2022). Formal collaboration facilitates regulatory capacity and access to financial and institutional resources, and informal collaboration fosters flexibility and trust in water governance processes in these regions (Evans et al, 2011;Tuda et al, 2021;Yasmin et al, 2022).…”
Section: Collaboration Across Sectors and Scalesmentioning
confidence: 99%
“…Following previous research in this field, Yasmin et al (2020), identified that community participation indicated that local actors' experience and expertise led to better opportunities in decisionmaking processes in water governance in Bangladesh. Tuda et al (2021) also identified how effective collaboration of diverse actors and multiple interactions foster AG of the Kenya-Tanzania transboundary marine socio-ecological systems that enhance cross-sectoral integration and create opportunities for multistakeholder bridging which is also found in water governance in South India (Vallury et al, 2022). Effective collaboration across sectors and scales initiatives had proven successful in enabling building leadership and trust among different stakeholders to minimize conflict and improve power sharing in a collaborative manner in cyclone management in India and Bangladesh (Walch, 2019;Choudhury et al, 2021).…”
Section: Collaboration Across Sectors and Scalesmentioning
confidence: 99%
See 3 more Smart Citations